Cybercrime as a Threat to National Security: A Review of the Role and Preparedness of the Indonesian Police - Abast, Brandon Romano; Damanik, Daniel Christian; Fahmi, Ghifari Jaya; Hutagalung, Jason Moreno Nanggala; Siahaan, Mario Tao Parsaulian (Proceedings of Police Academy, 2025)
The rapid advancement of digital technology has significantly altered the landscape of national security in Indonesia, with cybercrime emerging as a critical and complex threat. This study critically examines the role and preparedness of the Indonesian National Police (INP) in addressing cybercrime in the face of increasing digital vulnerabilities. Using a scoping review and thematic synthesis methodology, this research analyzes secondary data from scholarly publications, policy documents, and institutional reports to assess legal, institutional, and operational frameworks. Findings reveal that while the Indonesian government has established foundational measures, substantial challenges persist. These include a shortage of skilled personnel, low public digital literacy, fragmented inter-agency coordination, and outdated legal frameworks. To enhance national cyber resilience, this study recommends the strengthening of human capital through specialized training, improving inter-agency coordination protocols, updating legal instruments to match technological developments, expanding digital literacy campaigns, and fostering international cooperation. Ultimately, addressing cybercrime as a national security threat requires a cohesive, adaptive, and multi-sectoral policy approach. The findings aim to support future strategies to increase Indonesia’s capacity to prevent, respond to, and mitigate cyber threats effectively.